Faktor-faktor yang mempengaruhi minat mahasiswa dalam berorganisasi di kampus STIE Pancasetia - Fauziannor, Fauziannor (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This study aims to determine the partial and simultaneous influence, as well as the dominant influence of internal factors (X1) and external factors (X2) on student interest in organizing on the STIE Pancasetia campus (Y). This research is quantitative which intends to explain the causal relationship between variables through hypothesis testing. The population used in this study are active and less active students who follow the organization on the STIE Pancasetia campus. The number of members for the 2021/2022 period is 110 and the sample is 86 students. sample size using the Slovin formula. The results showed that the Internal Factor Variable (X1) had a significant effect on Organizational Interest (Y) at STIE Pancasetia Banjarmasin partially. External Factor Variables (X2) have a significant effect on Organizational Interest (Y) at STIE Pancasetia Banjarmasin partially, the influence of both Internal Factor variables (X1) and External Factors (X2), simultaneously (together) affect Organizational Interest (Y ) At STIE Pancasetia Banjarmasin. The results of the study stated that the variable that had the dominant influence on Interest in Organization was Internal Factor (X1), which means that Internal Factor (X1) had the strongest influence on Interest in Organization (Y) at STIE Pancasetia Banjarmasin. The variable with the most dominant influence on Interest in Organization (Y) at STIE Pancasetia Banjarmasin, because the partial r value of the Internal Factor variable (X1) is greater than the other variables.